Jumping through the hoops: Program planning practice in international development - Catherine C. Dunlop (Adult Education Research Conference, 1993)
This research looks at how the people involved in planning adult education programs in NGOs make sense of their practice and examines the strategies they use in the face of conflicting expectations and reliance on government funding.